KEMITRAAN STAKEHOLDERS DALAM PENGELOLAAN JALUR WISATA HERITAGE TRAINZ LOKO TOUR CEPU DI KABUPATEN BLORA - Nopi Dwi Indahsari; Agus Subianto; M. Husni Tamrin (REFORMASI, 2022)
The purpose of this study was to analyze the partnership between Perum Perhutani KPH Cepu and CV Hargo Dumilah Group in managing the Cepu Heritage Trainz Loko Tour tour route in Blora Regency. The Heritage Trainz Loko Tour Cepu tour is a tour package through the teak forest pulled by a steam locomotive made by Berliner Maschinnbau Germany in 1928. This research uses qualitative methods with a descriptive case study approach and focuses on the parameters of Commitment, Coordination of Interdependence, Trust, Communication Behavior with indicators of Communication Quality, Communication Sharing, Participation and Conflict Resolution Techniques. The results of the study show that tourism management is based on a cooperation agreement which contains the rights and obligations of each party and is running well. However, there were problems faced when the Covid-19 pandemic had an impact on tourism development which could not go according to plan. So it can be concluded that the indicator of trust is not optimal, this is due to problems that hinder sustainability in terms of development and arrangement of tourist objects.AsbtrakTujuan dari penelitian ini untuk menganalisa kemitraan antara Perum Perhutani KPH Cepu dengan CV Hargo Dumilah Group dalam pengelolaan jalur wisata Heritage Trainz Loko Tour Cepu di Kabupaten Blora. Wisata Heritage Trainz Loko Tour Cepu adalah paket perjalanan wisata melintasi hutan jati yang ditarik dengan lokomotif uap buatan Berliner Maschinnbau Jerman tahun 1928. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus deskriptif serta fokus pada parameter Commitment, Coordination of Interdependence, Trust, Communication Behavior dengan indikator Communication Quality, Communication Sharing, Participation and Conflict Resolution Techniques. Hasil penelitian menunjukkan bahwa pengelolaan wisata didasarkan atas perjanjian kerjasama yang memuat hak dan kewajiban dari masing masing pihak dan berjalan dengan baik. Namun terdapat permasalahan yang dihadapi saat adanya pandemi covid-19 berdampak pada pada pengembangan wisata yang tidak dapat berjalan sesuai rencana. Sehingga dapat disimpulkan bahwa indikator kepercayaan tidak optimal hal ini disebabkan adanya permasalahaan yang menghambat pada keberlangsungan dalam hal pembangunan maupun penataan pada objek wisata.